A theoretical framework for improving software project monitoring task of Agile Kanban method - Alaidaros, Hamzah; Omar, Mazni; Romli, Rohaida (Springer, 2018)
Progress monitoring task is one of the critical steps in the software project management (SPM). Consequently, successful realization of software projects is strongly associated with used method in implementing and monitoring those projects. Over the recent years, the adoption of Agile Kanban method is being increased, however, this method still having significant challenges in progress monitoring task during the process of software development. Therefore, this paper aims to draw upon relevant theories and conducts in-depth a review in order to establish a theoretical framework to improve the progress monitoring task of Agile Kanban method. Our findings revealed that three elements need improvements, which are progress tracking (PT), limiting work-in-progress WIP (LWIP), and progress visualization (PV). In addition, the three elements are aligned with theories, which are the explicit theory of project management (TETPM), progress monitoring theory (PMT), and the program theory (TPT). These findings extend the current literature on Agile software development by providing a holistic view on how progress monitoring task should be improved.